2013
DOI: 10.3109/01612840.2012.762958
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Treatment Engagement for Depression among Latinas

Abstract: In spite of successful treatment options for depression, the majority of Americans with severe depression do not receive treatment. Latinos are even less likely to engage in treatment than non-Hispanic Whites. The purpose of this study is to explore barriers to treatment engagement and, more specifically, how childhood adversity and gender-based violence (GBV) contribute to a lack of perceived support for treatment engagement. Experiences of GBV and childhood adversity can call into question deeply held family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 75 publications
1
22
0
1
Order By: Relevance
“…This finding is consistent with a valued belief among Latinos of doing one’s part in one’s recovery (“poner de su parte”) rather than relying on medication which is viewed as more passive [15,20,21]. The concept of poner de su parte is especially consistent with the framework of behavioral psychotherapies [22].…”
Section: Introductionsupporting
confidence: 74%
“…This finding is consistent with a valued belief among Latinos of doing one’s part in one’s recovery (“poner de su parte”) rather than relying on medication which is viewed as more passive [15,20,21]. The concept of poner de su parte is especially consistent with the framework of behavioral psychotherapies [22].…”
Section: Introductionsupporting
confidence: 74%
“…Job engagement can be defined as a positive and fulfilling state that is characterized by the vigor, and absorption of employees ( Schaufeli et al, 2002 ). In general, high job engagement means having a positive mental state on the job, and employees with high job engagement can be a particularly important variable in performance, because they improve organizational effectiveness, create more productive work environments, and reduce employee turnover ( Caplan and Whittemore, 2013 ).…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%
“…Their engagement strengthened when they realized the structure of the program was flexible and would work for their busy lives. However, Caplan and Whittemore (2013) found that Latinas with a past history of gender based violence or adversity in childhood may experience a diminishing ability to engage in depression treatment if their family does not support their quest to get treatment or if cultural values require women to hide problems to protect the reputation of the family. Furthermore, if gendered expectations call for Latinas who are mothers to endure emotional difficulties and remain silent, they may put off treatment.…”
Section: Discussionmentioning
confidence: 99%